Naturalismo e a abordagem responsabilista da epistemologia das virtudes - Ferreira Júnior, Eduardo Assis (2022)
Virtue epistemology is the branch of epistemology that place the notion of intellectual virtue as theoretically central in adressing fundamental epistemological questions, being divided into reliabilism and responsabilism, two different ways of understanding the notion of intellectual virtues. Unlike what happended with reliabilism, the responsabilist approach seems to have been developed with few naturalistic concerns and, due to the structural similarities between moral virtues and intellectual virtues, as well as the commitment of its normativity to some kinds of desirable dispositions that constitute the intellectual virtues, assuming the same kind of psychology as virtue ethics, the responsabilist approach is susceptible to situationist challenge. The present project sought to analyze whether the responsabilist approach to epistemology, in light of moderate epistemological naturalism and started form the hypothesis that is naturalizable. To do it, it proposes to distinguish naturalism projects contained in Alvin Goldman’s naturalism manual, in order to analyze responsabilism in the light of moderate epistemological naturalism and verify whether, in this perspective, the responsabilism of virtues counter-arguments respond satisfactorily to situationist challenge. Methodologically, the present work was divided into two types of researches: at first, the explanatory methody, bringing a bibliographic review that aims to characterize and define each approach and Project; in the second moment, the qualitative method, focused on subjective interpretations. The presente research leads to the assertation that Zagzebskian responsabilist approach does not satisfy all criteria of moderate epistemological naturalism and, therefore, is not naturalizable.